Cabaran dan dilema pendekatan pasca positivisme dalam perancangan bandar pintar di Malaysia - Jalaluddin Abdul Malek, (Universiti Kebangsaan Malaysia, 2005)
It is generally acknowledged that urban and rural planning in Malaysia is hitherto still patterned on the positivist colonial methodology such as ‘ surveys, analysis and plans’ as espoused by Petrick Geddes in the 1920s. This is evident in the historiography of urban and rural planning since the British colonial period in Malaya. The methodology of positivist planning which employs the ‘bottom-up’ approach continues to be based on colonial pragmatism. This trend was also evident in the colonial era, where the planning of towns was very much determined by the administration, hence making the people mere recipients of such planning. In order to continue the positivist approach and pragmatism of the government in the post- Independence period, a more systematic form of planning was introduced with the introduction of the Structural and Local Plans. Although both developmental plans were based on the concept of integrated planning under the Urban and Rural Planning Act 1976 (1972 Act), however development that ensued focussed more on the physical aspects with minimal emphasis on social requirements. The question remains, will the approach of positivism always be suitable for the planning needs of each era including planning for the intelligent city of today ? This has to be taken into consideration in view of the fact that, the planning of intelligent cities is intertwined with the era of instantaneous speed, its demands and space, all of which impact the changes and unlimited needs of man in the proses of globalization. Do only material and physical values need to be taken into account? What of humanitarian aspects which involve both ethical, moral and aesthetical values in planning? In addressing this problem, the work here discusses the post-positivism approach espoused by the Frankfurt School which argues for a value - added positivist method in the planning of intelligent cities in Malaysia